A new Thelastomathidae, Hammerschmidtiella laplatae n. sp. (Nematoda) parasite of the cockroach Periplaneta americana (L.) (Blattodea, Blattidae) from Argentina - Camino, Nora Beatriz (2018)
Hammerschmidtiella laplatae n. sp. (Nematoda, Thelastomatidae), a parasite of Periplaneta americana (L.) (Blattodea, Blattidae) from La Plata, Argentina, is described and illustrated. It is characterized by a striated cuticle with lateral alae, mouth with three triangular inner papillae, and eight labial papillae; small, pore-shaped amphids; short and wide buccal capsule with dental plates; an esophagus with a valvate metacorpus; a thin, cylindrical isthmus surrounded by the nerve ring; and a rounded basal bulb heavily muscled and valvate. The vulva is slightly protuberant and lies in the anterior third of the body. The female is didelphic and prodelphic. Small eggs, elongate, and triangular in cross-section. The male has one spicule, without gubernaculum; the genital papillae consist in one preanal and three postanal pairs, with the last pair being fingershaped. In the female the tail appendage is very long and thin; while in the male the posterior end of the body is abruptly truncated posterior to the anus with a long, spine-like tail appendage.